Mortality Inequality in England over the Past 20 Years. (29th April 2021) - Banks, James; Cattan, Sarah; Kraftman, Lucy; Krutikova, Sonya
Abstract: In this paper, we study the evolution of age‐group‐ and gender‐specific mortality and mortality inequality in England between 2003 and 2016, by comparing small geographic areas ranked by deprivation and grouped into bins of similar population size. We show that across all age groups, but especially in the older age groups (65+), there has been a clear and significant reduction in rates of mortality since 2003. In spite of these improvements, we continue to see significant inequalities in mortality across most age groups in 2016 and evidence of rising inequalities among women in the 65+ and men in the 80+ age groups. Furthermore, we see a striking stalling of the downwards trend in mortality and mortality inequality observed between 2003 and 2010 during the years of economic austerity in the aftermath of the 2008 financial crisis in England between 2010 and 2016. Analysis of specific causes of death among adults aged 20–79 allows us to examine the drivers and dynamics of these trends in more depth, as well as to consider scope for, and types of, interventions that would be appropriate at different ages.